Airborne collision severity study on engine ingestion caused by harmless-categorized drones - Liu, Hu (2021)
The drone weight less than 250g is often treated as a 'harmless' category by many authorities such as EASA (European Aviation Safety Agency) and CAAS (Civil Aviation Authority of Singapore). Is this small drone really safe and does not affect the operation of commercial aircraft? This paper is devoted to presenting a Finite Element Method (FEM) simulation method to analyze the performance of the commercial aircraft engine under the collision of the harmless categorized drone with a weight of 250g. The damage levels of the fan blades and compressor blades during the drone collision process are both investigated. Besides, another type of drone with a much higher weight (750g) is also analyzed to give a comparison study. The result shows no apparent damage to the aircraft engine fan blades, IGV, and LPC blades for the drone of MAVIC MINI, while some damage can be detected for the engine fan blades under the impact of the drone of MAVIC Pro.